1994
DOI: 10.1093/clinchem/40.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Two-site enzyme immunoassay of CD4 and CD8 molecules on the surface of T lymphocytes from healthy subjects and HIV-1-infected patients

Abstract: A highly sensitive two-site enzyme immunoassay (Capcellia) was developed to determine the concentration of CD4 and CD8 molecules expressed on the surface of human T lymphocytes. This assay, performed in one step (20 min), involves the specific immunocapture of T lymphocytes and reaction of the CD4 or CD8 molecules with an enzyme-labeled monoclonal antibody (mAb). The results were expressed as molar concentrations of the T-cell markers on the basis of results obtained with calibrated CD4 and CD8 standards. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…The coefficient of correlation was similar to that previously reported in a Caucasian population (Franke et al 1994). Carrière et al (1994) suggested an equivalence between pmol and number of cells: for CD4, 1 pmol ϭ 50 ϫ 10 6 cells/l and for CD8, 1 pmol/l ϭ 25 cells ϫ 10 6 /l. The sensitivity of the Capcellia assay is 0.9 pmol/l, which corresponds to 0.045 ϫ10 6 /l CD4 T lymphoctes.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The coefficient of correlation was similar to that previously reported in a Caucasian population (Franke et al 1994). Carrière et al (1994) suggested an equivalence between pmol and number of cells: for CD4, 1 pmol ϭ 50 ϫ 10 6 cells/l and for CD8, 1 pmol/l ϭ 25 cells ϫ 10 6 /l. The sensitivity of the Capcellia assay is 0.9 pmol/l, which corresponds to 0.045 ϫ10 6 /l CD4 T lymphoctes.…”
Section: Discussionsupporting
confidence: 89%
“…More and more people present with HIV infection in the developing world, so a less expensive method for their monitoring is needed. Alternative methods for the enumeration of CD4 T lymphocytes have been developed and evaluated (Carrière et al 1994;Nicholson Pinilla Moraza et al 1997). We compared concentrations of CD4 and CD8 molecules in circulating T cells given by the Capcellia assay (Carrière et al 1994) to CD4 ϩ and CD8 ϩ T lymphocyte numbers provided by cytofluorometry and haematology analysers.To compare the two methods within a wide range of absolute CD4 ϩ T lymphocyte counts, samples were collected from an AIDS clinic, a TB clinic and from healthy blood bank donors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering that both CD8αα and CD8αβ contain the CD8α chain, CD8α was chosen for the detection of CD8 molecules in this study. A double antibody sandwich enzyme-linked immunosorbent assay (DAS-ELISA) has previously been developed for the detection of human CD8 molecules (Carriere et al 1994) and is operational in distinguishing between healthy subjects and viral-infected patients. Recently, ELISA kits have emerged for using the recognition of goose CD8 (MyBioSource, Cat.…”
Section: Introductionmentioning
confidence: 99%